A Quality of Pharmaceutical Staff Services Over Out- Patients Satisfaction at Murni Teguh Sudirman Jakarta (MTSJ) Hospital - Peter Purwono; Rina Mutiara; M. Natsir Nugroho (Journal of Multidisciplinary Academic, 2021)
Services provided by hospital staff to patients greatly affects patient satisfaction. The cause of patient dissatisfaction can be caused by several factors including the service quality factor, such as Reliability, Assurance, Tangibles, Empathy and Responsiveness. Apart from that, there are 2 other factors that were examined this study, namely Accessibility and Communication. Thus, the problem in this study at Murni Teguh Sudirman Jakarta (MTSJ) Hospital there is decreased performance of pharmacy staff, so that there are complaints from outpatients to pharmacy service unit at MTSJ Hospital. Here analyses a quality of pharmaceutical staff services at out-patients satisfaction at MTSJ Hospital, also analyses the influence of Reliability, Assurance, Tangibles, Empathy, Responsiveness, Accessibility and Communication pharmaceutical staff services at out patients’ satisfaction at MTSJ Hospital. In addition, in this study we use a quantitative descriptive causality approach which aims to analyse relationships and influence (cause and effect) of two or more phenomena and correlation and regression analysis. The data collection techniques using is primary questionnaire with 5 Likert scale distributed to 49 respondents. The results shows that there is no influence from Reliability and Responsiveness pharmacy staff to out-patients satisfaction at MTSJ Hospital. There is influence from Assurance, Tangible, Empathy, Accessibility and Communication pharmacy staff and pharmaceutical installation to out-patients satisfaction at MTSJ Hospital, with value of correlation and regression analysis, if Significance values (Sig) < probability 0,05, then H0 (null hypothesis) be rejected and Ha (alternate hypothesis) accepted (there is no influence), if Significance values (Sig) > probability 0,05, then H0 (null hypothesis) accepted and Ha (alternate hypothesis) be rejected (there is influence).